2021
DOI: 10.1093/cid/ciab349
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathogenic Bacteria From Septic Patients Using 16S Ribosomal RNA Gene–Targeted Metagenomic Sequencing

Abstract: Background Conventional blood cultures were compared to plasma cell-free DNA–based 16S ribosomal RNA (rRNA) gene polymerase chain reaction (PCR)/next-generation sequencing (NGS) for detection and identification of potential pathogens in patients with sepsis. Methods Plasma was prospectively collected from 60 adult patients with sepsis presenting to the Mayo Clinic (Minnesota) Emergency Department from March through August 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Our study successfully demonstrated the advantage of mNGS in diagnosing pathogens via serum samples among patients with hematologic malignancies who developed sepsis. Previous studies have shown the superiority of NGS methods targeting the 16S ribosomal RNA gene in the diagnosis of bacterial infection among immunocompromised patients [18][19][20]. Metagenomic NGS further provides effective diagnostic approaches in diagnosing atypical pathogens such as virus, fungi, and mycobacterium [7,14], which are more commonly seen among patients with hematologic malignancies than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study successfully demonstrated the advantage of mNGS in diagnosing pathogens via serum samples among patients with hematologic malignancies who developed sepsis. Previous studies have shown the superiority of NGS methods targeting the 16S ribosomal RNA gene in the diagnosis of bacterial infection among immunocompromised patients [18][19][20]. Metagenomic NGS further provides effective diagnostic approaches in diagnosing atypical pathogens such as virus, fungi, and mycobacterium [7,14], which are more commonly seen among patients with hematologic malignancies than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative universal marker genes include the bacterial rpoB or the fungal internal transcribed spacer 1/2 (ITS-1/2) [ 84 ]. 16S sequencing has also been applied for clinical diagnostics, e.g., in abscesses [ 85 ], urinary tract infections [ 85 , 86 ], or sepsis [ 87 ], as well as for environmental studies. Oberaune et al profiled the microbiome of intensive care units (ICUs) and found higher microbial diversity compared to culture-dependent techniques [ 88 ].…”
Section: Focus On Bacterial Communitiesmentioning
confidence: 99%
“…Rip-seq (Pathogenomix Inc., Santa Cruz, CA, USA) for example, excludes non-informative or erroneous gene references from databases, resulting in rapid (5 min per analysis) and accurate identification of pathogens, even in polymicrobial samples. A recent study demonstrated that 16S rRNA gene sequencing using Illumina MiSeq coupled with Rip-Seq analysis was able to correctly identify pathogens with 58% concordance with blood culture results, including a polymicrobial case with E. coli and S aureus [97]. The discordant results were most likely due to sample preparation and issues with the assays, such as inhibition, interference from human DNA and the use of cell-free DNA, which has a short half-life [97].…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 99%
“…A recent study demonstrated that 16S rRNA gene sequencing using Illumina MiSeq coupled with Rip-Seq analysis was able to correctly identify pathogens with 58% concordance with blood culture results, including a polymicrobial case with E. coli and S aureus [97]. The discordant results were most likely due to sample preparation and issues with the assays, such as inhibition, interference from human DNA and the use of cell-free DNA, which has a short half-life [97]. A Breakthrough Device Designation has recently been granted by the FDA for the Patho-Seq assay (Pathogenomix Inc., Santa Cruz, CA, USA), which combines sequencing and Rip-Seq technologies for the identification of pathogens from different sample types (e.g., whole blood and CSF) and several clinical conditions, including polymicrobial sepsis.…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 99%